Rocksmith: desvelando relações de aprendizagem entre a guitarra elétrica e o jogo de videogame - Mota, Fernando de Sousa (2016)
The aim of this study was to understand the relation that two young people establish between the Rocksmith game and the electric guitar learning. From this main objective, we intended to describe the musical pedagogical aspects related to the game that are learned during the electric guitar learning; clarify the processes and manners of the electric guitar learning by means of the Rocksmith game and elucidate the musical learning to play guitar and play the game. The case study was the method adopted in this research in a qualitative approach. The procedures of data collection were the observation and the interview with the participants. The theoretical basis to the data analyses were: Souza (2004; 2014) to understand the musical education as social practice; Brougère (1998; 2002) to clarify the learning through the game; and Gee (2009) to understand the potential of the games to the learning. Among the conclusions, the Rocksmith game was able to relate the desire of the participants to learn playing electric guitar and their fascination with video games, besides to provide a new learning way of the electric guitar based on interaction between image and sound. The participants’ experience of playing a game with a ‘real electric guitar’ showed a tenuous threshold between the real and virtual of the Rocksmith game. Furthermore, this research showed that the Rocksmith game can be a valuable methodological approach to enhance the teaching and learning process of the electric guitar. Therefore, the electric guitar teachers should take advantage of the rise of games among the young people like a possibility to insert technological innovations in the music teaching and learning.